IT GOVERNANCE PADA DOMAIN DELIVER & SUPPORT (DS) PERBANKAN DENGAN MENGGUNAKAN MATURITY MODEL COBIT 4.1 (Studi Kasus pada Perbankan Wilayah Kota Semarang) - Ayu Noviani Hanum (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2011)
The aim of this research is to analyse the IT Governance on domain of Deliver and Support (DS) of thebanks by using Maturity Model COBIT 4.1. This domain is very important because it was related to the deliveryof required services, that consists the operations of security system and business sustainability to trainingprocess for their human resources.The respondent of this research was the Chief of Information Officer (CIO) of 8 banks in Semarang.This research was using scala 0-5, from Non Existence until Optimised level. The result of this research showsthat 6 banks were in Managed level, 1 bank in Defined level, and the other in Repeatable but Intuitive level.